TIPS FOR GETTING TRUE LOVE (A Truly Happy Relationship) - Indra Gunawan, Cakti (International Research & Development for Human Beings (IRDH), 2025)
True Love truly exists in this world. It appears amidst the chaos of human life. It shines like the moon, radiating an inner brilliance that originates from one’s conscience and reaches into the conscience of another. The reflection of that light from another person’s heart can also find its way back to the one who first radiated that love. Hopefully, this book can motivate readers to live life in a temporary world with enthusiasm and to reach God's grace, one of which is pursuing true love.